2024
DOI: 10.1007/s00705-023-05950-z
|View full text |Cite
|
Sign up to set email alerts
|

Detection and complete genome sequence analysis of human adenovirus in children with acute diarrhea in Yunnan, China, 2015–2021

Yihui Cao,
Jinghui Yang,
Nan Li
et al.

Abstract: The aims of this study were to determine the distribution and prevalence of gastroenteritis caused by human adenovirus (HAdV) in children in Yunnan province, China, in 2015–2021 and to identify preventive measures that can be taken to reduce morbidity and mortality in children.HAdV is a significant agent of diarrhea in children, but limited data are available regarding the epidemiology and genetic diversity of HAdV in children with diarrhea in Yunnan province, China. A total of 1754 fecal samples were subjecte… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Viral mNGS and confirmatory PCR testing in our cohort identified rare or novel potential links between pathogens to specific clinical entities ascertained using the VACC-Tool: three cases of ADEM could thus be linked to (a) saffold virus, (b) rotavirus, and (c) adenovirus detection [22] and one case of encephalitis was linked to sapovirus detection. All of these viral pathogens are frequently detected in patients with gastrointestinal disease, mainly presenting with acute diarrhea [33][34][35]. Diarrhea, however, was an exclusion criterion in our prospective digital surveillance and quality improvement program [13], meaning that the 100 clinical cases assessed in this study presented with confirmed CNS signs and symptoms in the confirmed absence of gastroenteritis.…”
Section: Discussionmentioning
confidence: 96%
“…Viral mNGS and confirmatory PCR testing in our cohort identified rare or novel potential links between pathogens to specific clinical entities ascertained using the VACC-Tool: three cases of ADEM could thus be linked to (a) saffold virus, (b) rotavirus, and (c) adenovirus detection [22] and one case of encephalitis was linked to sapovirus detection. All of these viral pathogens are frequently detected in patients with gastrointestinal disease, mainly presenting with acute diarrhea [33][34][35]. Diarrhea, however, was an exclusion criterion in our prospective digital surveillance and quality improvement program [13], meaning that the 100 clinical cases assessed in this study presented with confirmed CNS signs and symptoms in the confirmed absence of gastroenteritis.…”
Section: Discussionmentioning
confidence: 96%